ESTUDO E PROPOSTA DE MELHORIAS NA GESTÃO DE SEGURANÇA DE UNIDADES DE PETRÓLEO E GÁS, COM BASE NAS RECOMENDAÇÕES DAS AVALIAÇÕES DE RISCOS PARA SEGUROS - Bastos, José Guilherme Ribeiro Rodrigues de (2009)
The risks of extended industrial accidents that the great companies of Oil and Gas coexist make with that it is difficult of measure a possible damage proceeding from a fail in the safety of the productive process or of natural catastrophes, where occur losses of people, materials, damages to the environment something that affects its image. These massive investments in the Business Plans of the oil companies usually correspond to a considerable investment in HSE (Health, Safety and Environment) in the projects of their facilities, result from more end more restrictive regulations and technical national and international standards and the global need to attend international quality levels. With this increase in the investments, it has a clear trend of growth in the number of contract for new insurances or in the renewal of current for the oil and gas units. The evaluation work carried through companies specialized in risk analysis for insurances to oil and gas units is complex and highly specialized, with the employ of proper techniques. This is normally done by experienced professionals of the branch, coming from specialized international companies in the business. This dissertation, which focused Petrobras, had intended to study the main analysis methodologies and risk assessment applied for the determination of the quality of risk and the relation between investment in HSE and premium for insurances paid for oil and gas units. For this purpose are described, the basic characteristics of the main oil and gas units, the components of HSE management system of these companies, the methodologies used for the insuring and insured companies who act in this branch of activity and the main techniques of analysis and the main recommendation generated by professional risk assessment. The development of the work showed that not exist a standardized technique applied for evaluation of the premium insurance of these units, many times with its risks qualified of empirical form. However it is possible to improve the HSE management system of the oil and gas companies making use of the recommendations generated for insuring companies and, consequently, to contribute for reduction of the premium paid for the companies of this branch.